Evolutionary Computation, Machine Learning and Data Mining in Bioinformatics - Marchiori, Elena (Springer, 2017)
The field of bioinformatics has two main objectives: the creation and mainte-nance of biological databases, and the discovery of knowledge from life sciences data in order to unravel the mysteries of biological function, leading to new drugs and therapies for human disease. Life sciences data come in the form of biological sequences, structures, pathways, or literature. One major aspect of discovering biological knowledge is to search, predict, or model specific informa-tion in a given dataset in order to generate new interesting knowledge. Computer science methods such as evolutionary computation, machine learning, and data mining all have a great deal to offer the field of bioinformatics. The goal of the 6th European Conference on Evolutionary Computation, Machine Learning,and Data Mining in Bioinformatics (EvoBIO 2008) was to bring together experts from these fields in order to discuss new and novel methods for tackling complex biological problems.